2006
DOI: 10.1093/jac/dkl495
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of antimicrobial activity of the bacteriocin subtilosin A

Abstract: Background: Bacterocins are antimicrobial peptides produced by bacteria with a relatively narrow range of activity against closely related organisms. Subtilosin A is a bacteriocin produced by Bacillus subtilis that has activity against Listeria monocytogenes, which might indicate antimicrobial activity unusual for bacteriocins.Objectives: To examine the antimicrobial activity and factors affecting the activity of subtilosin A against a range of potentially pathogenic bacteria. Methods:The peptide was purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
122
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(130 citation statements)
references
References 10 publications
6
122
0
2
Order By: Relevance
“…The spectrum of activity was investigated and proved antagonism against a wide range of bacteria including Gram-positive and Gram-negative bacteria and both aerobes and anaerobes [18]. The production of mature subtilosin is based on the expression of the sbo-alb *Address correspondence to this author at the Department of Microbiology and Molecular Genetics, University of the Punjab, Quaid-e-Azam Campus, Lahore, Pakistan; Tel: +92-42-99238530; Fax +92-42-99230481: E-mail: shahida@mmg.pu.edu.pk, genetic@brain.net.pk gene cluster encompassing the subtilosin structural gene sbo and genes involved in posttranslational modification, processing of presubtilosin and immunity [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of activity was investigated and proved antagonism against a wide range of bacteria including Gram-positive and Gram-negative bacteria and both aerobes and anaerobes [18]. The production of mature subtilosin is based on the expression of the sbo-alb *Address correspondence to this author at the Department of Microbiology and Molecular Genetics, University of the Punjab, Quaid-e-Azam Campus, Lahore, Pakistan; Tel: +92-42-99238530; Fax +92-42-99230481: E-mail: shahida@mmg.pu.edu.pk, genetic@brain.net.pk gene cluster encompassing the subtilosin structural gene sbo and genes involved in posttranslational modification, processing of presubtilosin and immunity [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that with ScanAsyst mode the polysaccharide capsules could be detected even in the presence of deliquescent water covering the capsule. C apsular polysaccharide (CPS) plays important biological roles for many microorganisms, such as nutrient uptake (17), protection against environmental stresses (15), biofilm formation (8), and survival against phagocytosis or antibiotics (3,19,20). Moreover, CPS is potentially economically important material (2, 6, 7).…”
mentioning
confidence: 99%
“…Among the antimicrobials produced by B. subtilis 168 strains are sublancin (27), subtilosin A (2,35), bacilysocin (46), bacilysin (20,22,48), the SdpC sporulation delay toxin (8,14), the SkfA sporulation killing factor (1,14), and the TasA protein (37). The pleiotropic AbrB protein is known to play a role in regulating most of these antimicrobials in addition to numerous other genes expressed by postexponential-phase cells (22,31,36,37,54).…”
mentioning
confidence: 99%